When Spain believed that Katyn Could Win the War: Propaganda Vision of the Katyn Massacre by Intellectuals and Journalists of Franco’s Spain - da Costa, Marco (Populismo y propaganda: entre el presente y el pasado, 2020)
We propose to recall in this article the discovery, after 85 years, of the Katyn graves from the testimony of a series of Spanish journalists and intellectuals who, despite the uneasy socio-political situation in which the Franco regime lived after the setbacks of the Axis powers, would not hesitate to continue hoisting, from those famous massacres, the banner of totalitarianism as a bulwark in the defense of Western civilization against communist barbarism.